Study on Dry-Ice Particle Jet Polishing Process of 316L Stainless Steel Electrode. Issue 5 (January 2021) - Yang, Weiying; Feng, Xu; Xing, Yingjie; Pan, Weihao; Song, Jinlong
Abstract: Dry-ice particle jet technique has the advantages of rapid sublimation, easy drying, and without residues after striking onto the surface, which has been applied in the field of optical coating and the polishing and cleaning of integrated circuit. However, the process mechanism of this technique on stainless steel is not clear and the application research is not in-depth, which restricts the development and application of dry-ice particle jet technique in electrode polishing. In this work, the influence of the processing parameters such as spraying pressure, spraying angle, spraying distance, and spraying time on the micro-morphology and roughness of the stainless steel electrode surface was studied by single factor experiments. In addition, the characterization methods for the surface roughness, surface defects, surface micro-morphology, surface micro-unevenness, and surface chemical composition of the stainless steel electrodes were developed. Comprehensive characterization technology of the electrode surface was established.